Study of the antimicrobial activity and technological properties of a gel with catalpa bignonioides extract and dexpanthenol - Kovalev, Volodymyr; Oliinyk , Svitlana; Buryak , Maryna; Pul-Luzan , Viktoriya; Levachkova , Yuliya; Yakovenko , Oleksiy (Annals of Mechnikov’s Institute, 2024)
Introduction. To create and improve existing medicines for the local treatment of purulent wounds, an active search for plant substances with a pronounced antimicrobial effect is underway. At the Department of Pharmacognosy of the National University of Pharmacy, Associate Professor Demeshko O. V. obtained a dry extract of Catalpa bignonioides leaves. The chemical composition of the extract is represented by a wide range of biologically active substances and, above all, phenolic compounds, which exhibit high antimicrobial, anti-inflammatory, analgesic, diuretic and reparative activity. The wound healing and bactericidal effect of the bark, fruits and leaves of Catalpa bignonioides is explained by the presence of phytoncides in the plant. The chemical composition and wide range of therapeutic activity of the extract of Catalpa bignonioides leaves makes it promising for use in the development of medicines with antimicrobial action. Thus, the development of gels with dry (hydrophilic fraction) extract of catalpa leaves and the study of antimicrobial and technological properties of the developed gel is relevant. The purpose of the study. Technological properties and antimicrobial activity investigation of a gel containing hydrophilic extract of Catalpa Bignonia and Dexpanthenol for the wounds on the proliferation phase treatment. Materials &methods. The quality control of the developed gel products for the treatment of wounds and burns was carried out in accordance with the methods and recommendations given in SPhU 2.0., Volume 1, section "Soft medicinal products for dermal application". The results of the research were statistically processed in accordance with the requirements of SPhU 2.3 of Article 5.3. Results & discussion. Noveon is one of the popular polymers used in the production of medicinal products in gel form. Catalpa leaf extract concentrations as well as gel base composition were selected based on literature review and previous studies. The composition of the studied gel sample: Catalpa leaf extract – 5%, Dexpanthenol – 3%, polysorbate 80 – 5%, Noveon® – 1%, methylparaben – 0.001%, TEA to pH 5.0, purified water to 100%. The medicine under study looks like a homogeneous, transparent gel, light brown in color with a specific smell of catalpa extract. The obtained results show that when stored for 10 days at room temperature, the organoleptic properties of the gel sample did not change. The antimicrobial activity of the gel samples was determined by the agar diffusion method. The results of the research showed that the gel sample with Catalpa leaf extract – 5% has a weak sensitivity to Escher strains. Coli, Ps. Aeruginosa, Pr. vulg., Ps. aeruginosa and C. albicans; moderate to St. Aureus and Bac. Subtilis. The obtained data on the antimicrobial activity of the gel sample allow us to state that the antimicrobial activity of the gel sample did not change when stored for 10 days at room temperature. The pH of a 10% aqueous solution of the gel was investigated potentiometrically according to the method given in SPhU 2.0. According to the results of research, it was established that the pH of the sample is 5.42 ± 0.23. The effectiveness of therapy using drugs with high osmotic activity can significantly slow down wound healing. For use in the second and third stages of wound healing, the use of soft dosage forms with medium and low osmotic activity is recommended. The investigated gel sample exhibits low osmotic activity and adsorbs up to 26% of water within 8 hours of the experiment and does not damage the granulation tissue. Conclusion. The researched gel shows antimicrobial activity against the strains that are more often sown on wounds. The pH value is 5.42 ± 0.23, which indicates the possibility of using the gel in the treatment of burns. The osmotic properties of the gel were studied. The gel sample shows low osmotic activity and adsorbs approximately 26% of liquid in 8 hours. Key words: gel, extract of Catalpa bignonioides, technology, dexpanthenol.